Relación entre crecimiento económico y desigualdad en la distribución del ingreso: Caso colombiano en 23 departamentos y Bogotá en el periodo 2002-2018 (2020)
Latin America is one of the regions of the world that has been characterized by high levels of inequality in the distribution of income received by its inhabitants. The Colombian economy is not immune to this problem, and is highly concentrated in distribution due to the gaps in average income between departments, and due to the inequality, that exists among the population within geographical divisions. This paper seeks to determine the relationship between economic growth and inequality in income distribution in the 23 departments of Colombia and Bogotá in the period 2002-2018, through estimation by panel data, and the application of an econometric model using fixed coefficients, based on data collected from the National Administrative Department of Statistics (DANE). The main result is that the increase in income inequality has negative effects on economic growth in Colombia, which is why there is an inverse relationship between the variables studied. In addition, an estimate was made to determine whether there is a relationship between income inequality and human capital in Colombia with data obtained from the Penn World Table (PWT), where it is found that a large stimulus in human capital generates greater increases in income that in turn manage to boost development levels and reduce inequality in a country, that is, education is perceived as a determinant of balance, and its expansion allows for the economic well-being of a country.